2005
DOI: 10.1080/00207590444000221
|View full text |Cite
|
Sign up to set email alerts
|

The lay distinction between primary and secondary emotions: A spontaneous categorization?

Abstract: In line with the psychological essentialism perspective, Leyens et al. (2000) have hypothesized that people attribute different essences to groups and that they attribute more uniquely human characteristics to their own group than to out‐groups. Leyens et al. have focused on two types of emotions, which in Roman languages have specific labels, such as sentimientos and emociones in Spanish. A cross‐cultural study showed that sentimientos (or secondary emotions) are considered uniquely human emotions whereas emo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 15 publications
0
11
0
3
Order By: Relevance
“…Two coders blind to the hypotheses of the experiment were instructed to code the emotional attributes generated by participants in terms of humanizing or secondary (i.e., embarrassment, remorse, melancholy, shame, compassion, pride) and dehumanizing or primary (i.e., pleasure, happiness, desire, fear, pain, and rage). They were provided with a list of primary and secondary emotions which was composed drawing from the literature on infrahumanization (Demoulin et al, 2004;Leyens et al, 2000;Rodríguez-Torres et al, 2005). For example, a Romanian manager was described as proud, suspicious and frustrated, whereas a Romanian window-cleaner was described as hopeless, sad and scared (see Appendix).…”
mentioning
confidence: 99%
“…Two coders blind to the hypotheses of the experiment were instructed to code the emotional attributes generated by participants in terms of humanizing or secondary (i.e., embarrassment, remorse, melancholy, shame, compassion, pride) and dehumanizing or primary (i.e., pleasure, happiness, desire, fear, pain, and rage). They were provided with a list of primary and secondary emotions which was composed drawing from the literature on infrahumanization (Demoulin et al, 2004;Leyens et al, 2000;Rodríguez-Torres et al, 2005). For example, a Romanian manager was described as proud, suspicious and frustrated, whereas a Romanian window-cleaner was described as hopeless, sad and scared (see Appendix).…”
mentioning
confidence: 99%
“…Infrahumanization researchers (Demoulin et al, 2004;Rodriguez-Torres et al, 2005) have broadly confirmed that lay conceptions of primary and secondary emotions correspond to the guidelines set forth by emotion researchers (e.g., JohnsonLaird & Oatley, 1989). For example, Demoulin et al (2004) and Rodriguez-Torres et al (2005) set out explicitly to test whether laypeople drew a distinction between primary and secondary emotions similar to that which emotion researchers make.…”
Section: Searching With Webcorpmentioning
confidence: 79%
“…For example, Demoulin et al (2004) and Rodriguez-Torres et al (2005) set out explicitly to test whether laypeople drew a distinction between primary and secondary emotions similar to that which emotion researchers make. They used words categorized in the emotion literature as primary or secondary emotions, and found that people across cultures make distinctions between primary and secondary emotions corresponding with those used by emotion researchers (Demoulin et al, 2004).…”
Section: Searching With Webcorpmentioning
confidence: 98%
See 1 more Smart Citation
“…The distinction between primary (non-uniquely human) and secondary (uniquely human) is implicit and is spontaneously used in an intergroup context (Rodriguez-Torres, et al, 2005). This distinction is also used as a basis for intergroup discrimination.…”
Section: Infrahumanization and Reactions To Outgroupsmentioning
confidence: 99%